Study on Target Financial Forecasting as an Instrument to Overcome Financial Difficulties: Concept, Technique and Practice - Krylov, Sergey (New Innovations in Economics, Business and Management Vol. 6, 2022)
The paper examines the theoretical, methodological, and practical aspects of target financial forecasting at the micro level, i.e., at the company level, as a new tool for anti-crisis financial management that can help a company overcome financial difficulties and improve its financial position over virtually any time period. The research approach, as well as the findings given in the paper, is based on the concepts of financial ratio analysis, firm cash flows, and the Balanced Scorecard (in terms of its financial score). The procedure of target financial forecasting is depicted as consisting of an appropriate information-accounting support, a target financial forecasting of the company's financial position, a target forecasting of the company's cash flows, and the development of specific events (management's decisions) aimed at overcoming the company's financial difficulties and improving its financial position. According to the author, target financial forecasting is an efficient tool for financial forecasting in today's climate since it allows for the establishment of a foundation for overcoming a company's financial issues and increasing its financial position. The anti-crisis bankrupt company management, the management of a company on the verge of bankruptcy, and the development of a firm's investment appeal are the main sectors of the target financial forecasting application (in terms of its financial aspect).